The Death of Others. On the Narrative Rhetoric of Neoliberal Thanatopolitics - Jan Grue (Disability Studies Quarterly, 2022)
Euthanasia and physician-assisted suicide (PAS) are deeply controversial topics both within and beyond disability studies, involving issues of structural ableism, discrimination, and the right to self-determination. A common defence of the legalization of PAS, as distinct from euthanasia, rests on the right of an individual to freely choose when to end one's life. This essay makes an intervention in this debate by examining the rhetoric of media and cultural narratives that directly and indirectly address the issue of PAS and autonomous choice. Considering these narratives from a biopolitical point of view, I argue that contemporary thanatopolitical narratives draw on a particular rhetorical mode, known as "parrhesiastic rhetoric" or anti-rhetoric. This mode helps frame the testimony of extremely vulnerable individuals as a supremely credible argument in favor of the legalization of PAS. Moreover, it engenders sympathy rather than identification with these narrative subjects, ensuring that the death that is being justified remains at a distance from the reader, safely positioned as the death of others. I further argue that this narrative rhetoric supports a particular, neoliberal conception of autonomy, in which individual subjects are dynamic, rational and self-directing. In neoliberal thanatos political discourse, the choice to die is seen as fundamentally an outcome of individual, informed decision-making. Against this atomistic framework, I deploy the analyses of biopolitical disability studies to contribute to a better understanding of the historical, socio-economic, cultural, and rhetorical forces that shape contemporary debates over euthanasia and PAS.